Construction of Borders and Walls in Contemporary Ukrainian Literature (Analysis of Oleksandr Irvanets’ and Taras Antypovych Novels) (Altre Modernità, 2021)
Contemporary Ukrainian history offers fascinating cases of re-/de-bordering processes that provide evidence for how decision-makers and everyday citizens can change the historical course of the state. Border issues are particularly relevant to Ukraine, a country which has always been a borderland zone where many ethnic groups and cultures have interacted. For centuries, Ukraine has experienced multiple transformations of its territory, resulting from the influence of neighboring countries. In this paper we investigate how the image of the border is figuratively constructed in modern Ukrainian literature, paying particular attention to the shift in national self-identification caused by the collapse of the Soviet Union (1991) and national revolutions (2004, 2013-2014). We examine two dystopias of Ukrainian postmodern literature—Oleksandr Irvanets’ Rivne/Rovno (Stina) (2002) and Taras Antypovych’s Pomyrana (2016). Only fourteen years separate these novels, but this period was marked by crucial events in Ukrainian history—the Orange Revolution (2004) and the Revolution of Dignity (2013-2014). The first novel, Rivne/Rovno, represents an attempt to construct nationhood by parodying the Soviet past and the second, Pomyrana, allegorically reflects on Ukraine’s future during the Russia-Ukraine war (2014-present time). These texts reveal several literary images that need clarifying in the Ukrainian context: real border and mental border; shifting borders; border and identity; border as a means of inclusion or exclusion, etc. The paper envelopes Ukrainian identity issues within discussions of national identity, border and ‘otherness’ by examining how Ukrainian literature figuratively constructs recent changes of the national geobody.
Keywords: Ukrainian literature; Ukrainian identity; border; wall, self; other